Cyclopamine did not affect mouse oocyte maturation in vitro but decreased early embryonic development. (3rd June 2014) - Liu, Yang; Wei, Zhuying; Huang, Yafei; Bai, Chunling; Zan, Linsen; Li, Guangpeng
Abstract Hedgehog (Hh) pathway has been studied in various animal body life procedures and is suggested to be important for the development of multiple organs. The genes involved in the Hh signaling pathway were expressed in the ovary of mice, pigs and cattle. However, the function of Hh signaling pathway on oocyte maturation and early embryonic development is still controversial. We detected the effect of sonic hedgehog (Shh) and cyclopamine on the in vitro maturation of mouse oocytes and embryo development. The results showed that the presence of Shh or cyclopamine resulted in similar oocyte maturation to control groups. Shh did not improve early embryonic development. However, the supplement of cyclopamine depressed early embryo development. The mRNA of shh, ptch1, smo and gli1 were less detected in the denuded oocytes. The expression levels of ptch1 ascended from the uncleaved zygote to blastocyst stage. Smo or gli1 were expressed on a higher level at the two‐cell or four‐cell stage in early embryonic development separately. Therefore, Shh did not affect mouse oocyte maturation and early embryo development, but cyclopamine led to inhibited development of mouse early embryo. The effects of Hh signaling on the oocyte maturation and early embryo development might be species‐specific.